Rising Food Prices and Coping Strategies : Household-level Evidence from Afghanistan - D'Souza, Anna; Jolliffe, Dean (2012)
This paper investigates the impact of rising wheat prices -- during the 2007/08 global food crisis -- on food security in Afghanistan. Exploiting the temporal stratification of a unique nationally-representative household survey, the analysis finds evidence of large declines in real per capita food consumption and in food security (per capita calorie intake and household dietary diversity) corresponding to the price shocks. The data reveal smaller price elasticities with respect to calories than with respect to food consumption, suggesting that households trade off quality for quantity as they move toward staple foods and away from nutrient-rich foods such as meat and vegetables. In addition, there is increased demand in the face of price increases (Giffen good properties) for wheat products in urban areas. This study improves on country-level simulation studies by providing estimates of actual household wellbeing before and during the height of the global food crisis in one of the world's poorest, most food-insecure countries.